GERONTEKNOLOGI DAN PERAWATAN LANSIA - Naediwati, Ema Dessy (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
The growth of the elderly population has experienced a rapid increase in Indonesia. Elderly healthproblems alsohaveexperienced increase. Most old people want to stay at home instead of at a nursinghome or social institution. Elderly care at home focuses on improving quality of life, independenceand prevention of disability due to aging. The purpose of this literature study is related to the use ofgerontechnology in community-dwelling elderly. Literature study is conducted. The results of thethisstudy show that the use of gerontechnology can optimize the care of elderly who live at home.Gerontechnology is a term for professional fields that combine gerontology and technology. Manytypes of technology that can be used are assistive technologies, telehealth / telecare / telemedicine /telemonitoring / telesurveillance, virtual reality and gaming, social connectedness and smart home.Gerontological nurses play an important role in implementing gerontechnology especially inIndonesia. Nurses must be creative in their implementation due to the many challenges faced.Modification of technology with easy-to-find and inexpensive equipment can be developed.